Implementation of Hygiene and Sanitation in Novotel Hotel Kitchen, Tangerang - Amalia, Isma Nur; Elvandari, Milliyantri (Universitas Ibn Khaldun Bogor, 2024)
Hygiene is an effort to maintain health with a focus on individual actions and personal care, while sanitation is an effort to maintain the health of the human environment. Good hygiene and sanitation in hotel kitchens is essential to maintain food health and safety, as well as to meet food industry hygiene standards. In a clean and well-maintained kitchen environment, the risk of food contamination can be minimized, preventing food-borne illnesses and ensuring customer satisfaction. This article discusses important practices for maintaining hygiene and sanitation in hotel kitchens, including maintaining equipment cleanliness, waste management, personal hygiene, and staff training. Implementation of strict monitoring and control systems is also necessary to ensure the effectiveness of these efforts in maintaining high standards of hygiene throughout hotel kitchen operations. This research aims to evaluate how cleanliness and sanitation are implemented in the Novotel Tangerang hotel kitchen, including aspects such as personal hygiene, cleanliness and sanitation of the kitchen area, and maintenance of kitchen equipment. The research method used uses descriptive (qualitative) data analysis, using various primary data sources such as observations, interviews, and secondary data such as certificates and log books. Research findings show that even though observations, interviews and document recording have been carried out, cleanliness and sanitation standards in the Novotel hotel kitchen, Tangerang have been fully met. This can be seen from various aspects such as personal hygiene, kitchen sanitation, and cleanliness of kitchen equipment